If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + -2) * x = 3x(2x + 1) Reorder the terms: (-2 + x) * x = 3x(2x + 1) Reorder the terms for easier multiplication: x(-2 + x) = 3x(2x + 1) (-2 * x + x * x) = 3x(2x + 1) (-2x + x2) = 3x(2x + 1) Reorder the terms: -2x + x2 = 3x(1 + 2x) -2x + x2 = (1 * 3x + 2x * 3x) -2x + x2 = (3x + 6x2) Solving -2x + x2 = 3x + 6x2 Solving for variable 'x'. Reorder the terms: -2x + -3x + x2 + -6x2 = 3x + 6x2 + -3x + -6x2 Combine like terms: -2x + -3x = -5x -5x + x2 + -6x2 = 3x + 6x2 + -3x + -6x2 Combine like terms: x2 + -6x2 = -5x2 -5x + -5x2 = 3x + 6x2 + -3x + -6x2 Reorder the terms: -5x + -5x2 = 3x + -3x + 6x2 + -6x2 Combine like terms: 3x + -3x = 0 -5x + -5x2 = 0 + 6x2 + -6x2 -5x + -5x2 = 6x2 + -6x2 Combine like terms: 6x2 + -6x2 = 0 -5x + -5x2 = 0 Factor out the Greatest Common Factor (GCF), '-5x'. -5x(1 + x) = 0 Ignore the factor -5.Subproblem 1
Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0Subproblem 2
Set the factor '(1 + x)' equal to zero and attempt to solve: Simplifying 1 + x = 0 Solving 1 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + x = 0 + -1 x = 0 + -1 Combine like terms: 0 + -1 = -1 x = -1 Simplifying x = -1Solution
x = {0, -1}
| 58=-2(m+4)m | | r^2-19t+18=0 | | r^2-9t+18=0 | | 1000=x(30-2x)(20-2x) | | -30a=-20 | | -30=-20 | | 7x-14=11x | | -2x-4=24 | | -2(2x-6)=20 | | -2(x+5)=30 | | 2(2x-6)=40 | | 4x-2x+2=16 | | x-5x+4=-8 | | 2x+8x=17 | | -7x+5x+2=20 | | x-8-3=10 | | 8z=40 | | 24x-3=15+45x | | 9t=-16t^2+60t | | -13y-7y=-140 | | 2x-7=20+12x | | 13y-7y=-140 | | -10x-3x=-39 | | 3x+4y+z= | | -4x-8x=48 | | 60*0-30x=-180 | | c=a+ab | | 3a(n+7)=43 | | 60y-30x=-180 | | 3p^2+12p+11=0 | | 3(2x-3)=63 | | c=(a*b)+a |